Monitoring COVID-19 Impacts on Households in South Sudan, Report No. 1 : Results from a High-Frequency Phone Survey of Households - Finn, Arden (World Bank, Washington, DC, 2020)
There is an urgent need for timely data to help monitor and mitigate the social and economic impacts of the Coronavirus (COVID-19) pandemic and protect the welfare of the South Sudanese citizens. To respond to this need, the World Bank designed and conducted a rapid phone-based Household Monitoring Survey (HMS). This brief summarizes the results of the first round of the HMS, implemented between June 9 and June 25, 2020.